Economic efficiency and organization of the productive chain of honey in Campeche, Mexico - Pat Fernández, Lucio Alberto; Romero Durán, H. Paulina; Anguebes-Franceschi, Francisco; Pat Fernández, J. Manuel (Agricultura, Sociedad y Desarrollo, 2020)
The global food market, based on strict sanitary and quality standards, imposes new challenges to production and marketing by small-scale producers in developing countries. In this article the economic efficiency of small-scale beekeepers is examined, as well as the relationships between actors and the functioning of the honey chain in Campeche, Mexico. The information was obtained through in-depth interviews with key informants, and community workshops. The results show that the conventional honey chain is efficient, although it favors large cooperatives and private trading companies due to economies of scale. Small-scale producers and their organizations can increase their competitiveness through differentiation of the product and diversification of the activity, but only if they are capable of establishing new agreements with other actors of the chain. In addition, the government can favor the development of these organizations and promote commercial, technological and institutional innovations between actors of the chain.